Response of the topside and bottomside ionosphere at low and middle latitudes to the October 2003 superstorms - Lei, Jiuhou (2015)
Ionospheric observations from the ground‐based GPS receiver network, CHAMP and GRACE satellites and ionosondes were used to examine topside and bottomside ionospheric variations at low and middle latitudes over the Pacific and American sectors during the October 2003 superstorms. The latitudinal variation and the storm time response of the ground‐based GPS total electron content (TEC) were generally consistent with those of the CHAMP and GRACE up‐looking TEC. The TECs at heights below the satellite altitudes during the main phases were comparable to, or even less than, the quiet time values. However, the storm time CHAMP and GRACE up‐looking TECs showed profound increases at low and middle latitudes. The ground‐based TEC and ionosonde data were also combined to study the TEC variations below and above the F2 peak height (hmF2). The topside TECs above hmF2 at low and middle latitudes showed significant increases during storm time; however, the bottomside TEC below hmF2 did not show so obvious changes. Consequently, the bottomside ionosphere made only a minor contribution to the ionospheric positive phase seen in the total TEC at low and middle latitudes. Moreover, at middle latitudes F2 peak electron densities during storm time did not have the obvious enhancements that were seen in both the ground‐based and topside TECs, although they were accompanied by increases of hmF2. Therefore, storm time TEC changes are not necessarily related to changes in ionospheric peak densities. Our results suggest that TEC increases at low and middle latitudes are also associated with effective plasma scale height variations during storms.